Rancang Bangun Mesin Pengupas Kulit Kacang Tanah Menggunakan Motor Listrik Dengan Tipe Silinder Horizontal Menggunakan Bahan Pisau ST 37 - Anderson, Sir; Yuliarman, Yuliarman; Maimuzar, Maimuzar; Nasirwan, Nasirwan; Nusyirwan, Nusyirwan; Nofriadi, Nofriadi; Elisma, Netri; Insani, Farhan Filza (Politeknik Negeri Padang, 2024)
Peanuts are a plant that is widely cultivated in Indonesia, but the process of peeling the skin is still often done manually, which requires a lot of time and effort. To increase efficiency in this process, a peanut peeling machine with a horizontal cylinder design was developed. This innovation is designed to make it easier for farmers and small entrepreneurs to peel peanuts with a larger production capacity. This peeling machine is equipped with a nut discharge regulation system and uses a 1 Hp electric motor with a speed of 1400 rpm which is transmitted to 700 rpm. The stripping process is carried out by putting the dried peanuts into the hopper, then the knife cylinder rotates to separate the husks from the peanuts. The system is supported by a belt and pulley mechanism that ensures smooth operation of the machine. The test results showed that this machine was able to peel peanuts with a capacity of 64 kg/hour, providing a significant increase in productivity when compared to manual methods. This machine is expected to provide a more efficient solution for the agricultural industry and home businesses in peanut processing.